Digital Learning Content Development Digital Learning Content Strategy in the Era Society 5.0 - Hendrawati, Titi; Suherman, Suherman (Riwayat: Educational Journal of History and Humanities, 2025)
This article discusses the importance of digital learning content development in the context of Society 5.0, where collaboration between technology and humans is key to creating an inclusive and sustainable society. The research identifies the challenges educational institutions face in adapting traditional learning methods to digital formats, as well as the need to design content that is engaging and responsive to student needs. In the Islamic perspective, education is considered an obligation that should be done with spiritual awareness, so the development of digital content should include moral and ethical values. This article suggests strategies such as student needs analysis, the use of interactive technologies such as augmented reality and gamification, and project-based approaches to increase student engagement. In addition, the importance of training for educators and collaboration between stakeholders is emphasized to overcome resistance to change and improve technological infrastructure. By implementing these strategies, educational institutions are expected to create more effective and engaging learning experiences in the digital age.